Nepal Vegetable Seed Study: Retailer Survey - International Food Policy Research Institute; Seed Entrepreneur Association Nepal (International Food Policy Research Institute, 2018)
This study contains data that were collected to assess the status of vegetable seed retailers and markets across Nepal. The data contains information from 98 retailers from 20 districts in Nepal. The data collected includes information on vegetable seed retailers inventory and purchases and buyers of vegetable seeds.